GUIDED CONVERSATION TECHNIQUE IN EFL CLASSROOMS: SUPPORTING SPEAKING SKILLS DEVELOPMENT - Mulki, Nur; Meisuri, Meisuri; Rahmawati, Istiqomah Nur (Universitas Muhammadiyah Metro, 2025)
This study explored the implementation of guided conversation techniques in supporting speaking skills development among tenth-grade EFL students through a qualitative descriptive approach. Data were collected using semi-structured interviews and guided classroom observations. Findings indicated that the guided conversation technique positively influenced students' speaking proficiency, notably in fluency, vocabulary mastery, pronunciation, grammar, and sentence construction. Importantly, students reported increased confidence and reduced anxiety when speaking English, highlighting the emotional benefits of structured conversational practice. Observations also confirmed increased student participation, interaction, and engagement, supported by consistent and constructive teacher feedback. While some students still encountered challenges such as pronunciation difficulties and shyness, ongoing teacher support significantly mitigated these issues. Overall, the guided conversation technique emerged as a practical instructional approach, enhancing both linguistic skills and emotional readiness in EFL classrooms. Recommendations include incorporating differentiated scaffolding and further qualitative research in varied educational contexts.